Case Report: Diagnostic challenges in VEXAS syndrome with novel ultrastructural lung findings: IgG4-RD and vasculitis as relevant differential diagnoses - Etzel, Peter; Lang, David; Öberseder, Gregor; Lamprecht, Bernd (Frontiers in Immunology, 2026)
VEXAS syndrome is a rare, adult-onset autoinflammatory disorder caused by somatic mutations in the UBA1 gene. Patients may present with symptoms similar to IgG4-related disease (IgG4-RD) or systemic vasculitis. We report the case of a 70-year-old man who presented with periorbital swelling, fever, and elevated serum IgG4. However, a biopsy of the lacrimal gland did not show histological evidence of IgG4-RD. Consecutively, the patient developed progressive pulmonary infiltrations, bicytopenia and leukocytoclastic vasculitis. Chest-CT showed organizing pneumonia, which was histologically proven by transbronchial lung cryobiopsy (TBLC), again excluding IgG4-RD. PET/CT revealed hypermetabolic bone marrow and bone marrow aspiration biopsy showed vacuolization of granulocytic precursor cells. Finally, genetic testing for UBA1 mutation confirmed the diagnosis of VEXAS syndrome. Treatment with ruxolitinib in addition to steroids, led to temporary stabilization but long-term prognosis was unfavorable. This case highlights the importance of considering VEXAS syndrome a relevant differential diagnosis of vasculitis and IgG4-RD in men. Furthermore, we present valuable insights into the pathophysiology of VEXAS through transmission electron microscopy (TEM) of TBLC samples.